Resistin—A Novel Feature in the Diagnosis of Sepsis in Premature Neonates - Gokmen, Zeynel; Ozkiraz, Servet; Kulaksizoglu, Sevsen; Kilicdag, Hasan; Ozel, Deniz; Ecevit, Ayse; Tarcan, Aylin (American Journal of Perinatology, 2013)
Objective To evaluate the diagnostic potential of resistin in sepsis and to compare results with C-reactive protein (CRP) in infants < 32 weeks of gestation.Study Design A total of 64 infants were prospectively included in the study. Blood samples were collected for basal CRP and resistin within the first hour of life. When sepsis was suspected, samples were collected for CRP and resistin before the treatment was started (pretreatment CRP and resistin). On the third day of sepsis, CRP and resistin levels were measured for evaluating the treatment response (follow-up CRP and follow-up resistin). Culture-proven septic patients were divided into groups according to early or late-onset sepsis (EOS and LOS) and gram-negative or gram-positive sepsis (GNS and GPS).Results Pretreatment and follow-up resistin levels were significantly higher than basal resistin levels in both EOS and LOS groups (p < 0.01), with a positive correlation with CRP levels. To predict the GNS and GPS area under curve, values of pretreatment CRP and resistin were 0.714 and 0.984, respectively (p = 0.039).Conclusion Resistin had a superior potential to that of CRP in the diagnosis of sepsis in preterm infants. Resistin may be used as an early marker for sepsis in premature infants.
Keywords: resistin; sepsis; newborn; premature infants; C-reactive protein